Assessment of Risk Factors of Ischemic Mitral Regurgitation Post Myocardial Infarction - Sajid Ali, Muhammad Muzamil, Ahmad Tariq (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: The study was conducted to assess the incidence of papillary muscle involvement, severity of left ventricular infarction and risk factors of ischemic mitral regurgitation after myocardial infarction. Methodology: This retrospective study was conducted in the Department of Cardiology of PIC Lahore from December 2021 to June 2023. A total of 100 patients with severe heart attack as a result of chronic artery disease undergoing cardiac magnetic resonance and ECG were included in the study by consecutive sampling. The degree of ischemic mitral regurgitation was measured by standard PISA method given by European cardiovascular association. The cardiac functionality and structure along with extent of infarcted tissue was examined by cine CMR and LGE CMR, respectively by cardiac magnetic resonance. Results: Among the 100 patients included, 55 patients (55%) had a grade I ischemic mitral regurgitation and 45 patients (45%) had grade II-III ischemic mitral regurgitation. Papillary muscle infarction was found in 20 patients (20%) with posteromedial and anterolateral infarct in 5 patients each and 10 patients had both. Seven patients (35%) had mild regurgitation and 13 patients (65%) had moderate-to-severe regurgitation. Multivariate analysis showed age (OR: 1.08 (95% CI: 1.03-1.23), p=0.001), degree of infarction (OR: 1.16 (95% CI: 1.09-1.20), p=0.000) and global longitudinal strain (OR: 1.28 (95% CI: 1.18-1.47), p=0.000) were independent risk factors of grade II-III regurgitation. Conclusion: It is concluded that There is high incidence of papillary muscle infarction in patients with grade II-III ischemia mitral regurgitation. Age, degree of infarction and global longitudinal strain independent risk factors of grade II-III regurgitation. Keywords: Ischemic Mitral Regurgitation, Post Myocardial Infarction, left ventricular infarction, Cardiology